Analisis Perbandingan Simpangan Lateral Bangunan Tinggi dengan Variasi Bentuk dan Posisi Dinding Geser. Studi Kasus: Proyek Apartemen The Royale Springhill Residences - Aswin Hasan; Imron Fikri Astira (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2013)
A building should at least be able to bear the loads that work on the structure . Lateral loads such as wind loads and seismic loads that can cause lateral deflection and gravity loads including dead load and live load. The higher the building , the lateral deflection occurs also greater in atas. Structure Engingeer planners are required to better understand the design of earthquake resistant structures that are not just simply follow in designing the building , but must comply with the Earthquake Resilience Planning Procedures for Building a goal is for earthquake resistance of building structures are planned to function properly in designing a building structure must be considered rigidity , stability of the structure withstand any loading imposed on them and how the behavior of the structure to withstand such loads . ETABS is a 3D Extended program of Building Systems of Computer and Structure inc that use the Windows operating system . The use of simulation program ETABS memperlihat pattern collapse was going to happen so it can be input for the planning and construction of high-rise buildings better . In this study will be compared to the horizontal deflection obtained from the comparison position and shape shear walls . Results from this research is a comparison of deflection that occurs , a review of the limits of serviceability and ultimate limit each building models to be compared .Keywords: high rise buildings, diplacement, etabs, shearwall